Representasi Disabilitas dalam Iklan 'We’re the Superhumans' - Niyu, Niyu (PLD UIN Sunan Kalijaga, 2017)
Disability is not something that is 'invisible', but it is something real and present among us. Media, especially television through advertising, has a significant role in creating perceptions about disability and to change the paradigm of people on disability. This research discusses how Channel 4 (C4) through